Identification of a Novel Mutation in the PAH Gene in an Iranian Phenylketonuria Family: A Case Report - Masoumeh RAZIPOUR; Daniz KOOSHAVAR; Elaheh ALAVINEJAD; Seyede Zahra SAJEDI; Neda MOHAJER; Aria SETOODEH; Saeed TALEBI; Mohammad KERAMATIPOUR (Tehran University of Medical Sciences, 2017)
Phenylketonuria (PKU) is an inborn error of amino acid metabolism with an autosomal recessive inheritance caused in most cases by mutations in the phenylalanine hydroxylase (PAH) gene. PKU has wide allelic heterogeneity. Here we report a novel heterozygous substitution (c.1223G>T (p.Arg408Leu)) in the PAH gene in an Iranian PKU family. The patient was 19-yr-old female with diagnosis of moderate PKU referred to Department of Medical Genetics, Tehran University of Medical Sciences, Tehran, Iran for genetic counseling/analysis in April 2015. We used PCR-Sequencing to identify any sequence variations in the PAH gene.